Pembuatan Minuman Fermentasi Sari Tomat dengan Menggunakan Lactobacillus casei subsp. casei R-68 - Novri Oksianus Harahap; Vonny Setiaries Johan; Usman Pato (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Tomato is a fruit that had a short shelf life.Therefore tomato needs to be processed into products that have economic value, such as fermented drink. The purpose of this research was to obtain the best addition of sucrosein makingfermented drink of tomato juice by using Lactobacillus casei subsp. caseiR68. This research used a Completely Randomized Design with four treatments and four replications. The treatments used were P1 (without addition of sucrose), P2 (addition of sucrose 9%), P3 (addition of sucrose 12%), and P4 (addition of sucrose 15%). The result showed that addition of sucrose significantly affected total lactid acid bacteria (LAB), total lactid acid, and ash content but did not significantly affected pH. The chosen treatment from this research was the treatment P3 (addition of sucrose 12%) which P3 had pH 4.05, total LAB 10.32 log cfu/ml, total lactid acid 0.70%, sucrose content 10.39% and ash content 0.78%.Keywords:Fermentation drink, tomato juice, sucrose, lactid acid bacteria, Lactobacillus casei subsp.casei R-68